STRATEGI PENYANDANG DISABILITAS DALAM PEMENUHAN KEBUTUHAN SOSIAL EKONOMI (Studi Pada Perkumpulan Penyandang Disabilitas Indonesia (PPDI) Provinsi Sulawesi Tenggara) - Amaliah, Henni; Hos, Jamaluddin; Tanzil, Tanzil (WELL-BEING: Journal of Social Welfare, 2020)
Persons with disabilities are every person who experiences physical, intellectual, mental and or sensory limitations for a long period of time who in interacting with the environment may experience obstacles and difficulties to participate fully and effectively with other citizens based on equal rights. The purpose of this research is to find out how the strategies of persons with disabilities in meeting their socio-economic needs. This research method is descriptive qualitative. The results showed that first, the strategies carried out by members of PPDI Southeast Sulawesi in fulfilling their social needs were building their self-confidence by working and also joining an environment that had conditions like them, getting social support from fellow members by sharing experiences and support. family, build social networks by increasing the number of friends they can invite to work together. Second, the strategy to fulfill the economic needs of PPDI Southheast Sulawesi members is to attend training such as entrepreneurship training, sewing training, cooking training and massage training. Entrepreneurship, members of PPDI Southheast Sulawesi can improve their economic level with entrepreneurship. And have a side job that can increase their source of income and also improve their abilities.Â